Co-assembly of HPV capsid proteins and aggregation-induced emission fluorogens for improved cell imaging. Issue 9 (24th February 2020) - Jing, Jiangbo; Xue, Ya-Rong; Liu, Yu-Xue; Xu, Bin; Li, Hong-Wei; Liu, Leijing; Wu, Yuqing; Tian, Wenjing
Abstract : A co-assembly of HPV capsid protein L1 and an AIE molecule DSAI has been constructed via the bridge of dsDNA, ensuring their improved ability for cell imaging. Abstract : In order to improve the cell-imaging ability, and particularly, to extend the bio-application of AIEgen, human papillomavirus (HPV) capsid protein L1 was assembled with the complex of DNA and aggregation-induced emission fluorogen 9, 10-distyrylhydrazine (DSAI), where the virus-like particles (VLPs) of HPV encapsulate the complex via electrostatic interaction. The co-assembled nanoparticles, DSAI-DNA@VLPs, showed homogeneous size (∼53 nm), enhanced fluorescence (8 × 2.5-fold), considerable stability (anti-DNase digestion), improved biocompatibility and commendable protection for the DSAI-DNA complex, ensuring virtual brighter imaging in live cells, both for HeLa and normal 293T cell lines.